[go: up one dir, main page]

login
A048736
Dana Scott's sequence: a(n) = (a(n-2) + a(n-1) * a(n-3)) / a(n-4), a(0) = a(1) = a(2) = a(3) = 1.
28
1, 1, 1, 1, 2, 3, 5, 13, 22, 41, 111, 191, 361, 982, 1693, 3205, 8723, 15042, 28481, 77521, 133681, 253121, 688962, 1188083, 2249605, 6123133, 10559062, 19993321, 54419231, 93843471, 177690281, 483649942, 834032173, 1579219205, 4298430243, 7412446082, 14035282561, 38202222241, 65877982561
OFFSET
0,5
COMMENTS
The recursion has the Laurent property. If a(0), a(1), a(2), a(3) are variables, then a(n) is a Laurent polynomial (a rational function with a monic monomial denominator). - Michael Somos, Feb 05 2012
A generalization is if the recursion is modified to a(n) = (a(n-2) + a(n-1) * b*a(n-3)) / a(n-4) where b is a constant, and with arbitrary nonzero initial values, (a(0), a(1), a(2), a(3)), then a(n) = c*(a(n-3) - a(n-6)) + a(n-9) for all n in Z where c is another constant. - Michael Somos, Oct 28 2021
LINKS
Seiichi Manyama, Table of n, a(n) for n = 0..3165 (first 501 terms from T. D. Noe)
Joshua Alman, Cesar Cuenca, and Jiaoyang Huang, Laurent phenomenon sequences, Journal of Algebraic Combinatorics 43(3) (2015), 589-633.
Hal Canary, The Dana Scott Recurrence [From Jaume Oliver Lafont, Sep 25 2009]
S. Fomin and A. Zelevinsky, The Laurent phenomenon, arXiv:math/0104241 [math.CO], 2001.
S. Fomin and A. Zelevinsky, The Laurent Phenomenon, Advances in Applied Mathematics, 28 (2002), 119-144.
David Gale, The strange and surprising saga of the Somos sequences, Math. Intelligencer 13(1) (1991), pp. 40-42.
D. Gale, Tracking the Automatic Ant And Other Mathematical Explorations, A Collection of Mathematical Entertainments Columns from The Mathematical Intelligencer, Springer, 1998, p. 4.
Matthew Christopher Russell, Using experimental mathematics to conjecture and prove theorems in the theory of partitions and commutative and non-commutative recurrences, PhD Dissertation, Mathematics Department, Rutgers University, May 2016.
Eric Weisstein's World of Mathematics, Laurent Polynomial
FORMULA
a(n) = 9*a(n-3) - a(n-6) - 3 - ( ceiling(n/3) - floor(n/3) ), with a(0) = a(1) = a(2) = a(3) = 1, a(4) = 2, a(5) = 3. - Michael Somos
From Jaume Oliver Lafont, Sep 17 2009: (Start)
a(n) = 10*a(n-3) - 10*a(n-6) + a(n-9).
G.f.: (1 + x + x^2 - 9*x^3 - 8*x^4 - 7*x^5 + 5*x^6 + 3*x^7 + 2*x^8)/(1 - 10*x^3 + 10*x^6 - x^9). (End)
a(n) = a(3-n) for all n in Z. - Michael Somos, Feb 05 2012
EXAMPLE
G.f. = 1 + x + x^2 + x^3 + 2*x^4 + 3*x^5 + 13*x^6 + 22*x^7 + 41*x^8 + 111*x^9 + ...
MATHEMATICA
RecurrenceTable[{a[0] == a[1] == a[2] == a[3] == 1, a[n] == (a[n - 2] + a[n - 1]a[n - 3])/a[n - 4]}, a[n], {n, 40}] (* or *) LinearRecurrence[{0, 0, 10, 0, 0, -10, 0, 0, 1}, {1, 1, 1, 1, 2, 3, 5, 13, 22}, 41] (* Harvey P. Dale, Oct 22 2011 *)
PROG
(Haskell)
a048736 n = a048736_list !! n
a048736_list = 1 : 1 : 1 : 1 :
zipWith div
(zipWith (+)
(zipWith (*) (drop 3 a048736_list)
(drop 1 a048736_list))
(drop 2 a048736_list))
a048736_list
-- Reinhard Zumkeller, Jun 26 2011
(PARI) Vec((1+x+x^2-9*x^3-8*x^4-7*x^5+5*x^6+3*x^7+2*x^8) / (1-10*x^3+10*x^6-x^9)+O(x^99)) \\ Charles R Greathouse IV, Jul 01 2011
(Magma) I:=[1, 1, 1, 1]; [n le 4 select I[n] else (Self(n-2) + Self(n-1)*Self(n-3)) / Self(n-4): n in [1..30]]; // G. C. Greubel, Feb 20 2018
CROSSREFS
Cf. A192241, A192242 (primes and where they occur).
Cf. A276531.
Sequence in context: A177374 A142881 A163159 * A235621 A193300 A215310
KEYWORD
nonn,easy,nice
EXTENSIONS
More terms from Michael Somos
STATUS
approved